Stakeholder Governance for Responsible Innovation: A Theory of Value Creation, Appropriation, and Distribution - Bacq, Sophie; Aguilera, Ruth V. (Journal of Management Studies, 2022)
AbstractIn the face of intractable societal grand challenges, organizations increasingly resort to responsible innovation – that is, they pledge to create value for multiple stakeholders through developing new products or services that avoid doing harm and improve conditions for people and the planet. While the link between responsible innovation and societal improvements has been established, organizations pursuing responsible innovation lack governance mechanisms to guide the allocation of the value created – both economic and social – among heterogeneous stakeholders, in line with their responsible intent. We combine the value‐based strategy and stakeholder perspectives and infuse a deliberative process to design a three‐stage model of value allocation that rests on three key organizational decisions: i) what value to create and for whom, ii) how to appropriate the value created vis‐à‐vis unintended value appropriators, and iii) how to distribute the value appropriated among intended stakeholders. We propose a framework of stakeholder governance comprised of four novel mechanisms by which organizations can allocate value among their multiple principal stakeholders as part of participative processes. Our study contributes to responsible innovation and corporate governance research by unpacking how new value is managed to solve societal grand challenges.